The functional interlink between AR and MMP9/VEGF signaling axis is mediated through PIP5K1α/pAKT in prostate cancer. Issue 6 (16th August 2019) - Larsson, Per; Syed Khaja, Azharuddin Sajid; Semenas, Julius; Wang, Tianyan; Sarwar, Martuza; Dizeyi, Nishtman; Simoulis, Athanasios; Hedblom, Andreas; Wai, Sun Nyunt; Ødum, Niels; Persson, Jenny L.
Abstract : Currently, no effective targeted therapeutics exists for treatment of metastatic prostate cancer (PCa). Given that matrix metalloproteinases 9 (MMP9) and its associated vascular endothelial growth factor (VEGF) are critical for tumor vascularization and invasion under castration‐resistant condition, it is therefore of great importance to define the functional association and interplay between androgen receptor (AR) and MMP9 and their associated key survival and invasion pathways in PCa cells. Here, we found that there was a significant correlation between MMP9 and AR protein expression in primary and metastatic PCa tissues, and a trend that high level of MMP9 expression was associated with poor prognosis. We demonstrated that constitutive activation of AR increased expression of MMP9 and VEGF/VEGF receptors. We further showed that AR exerts its effect on MMP9/VEGF signaling axis through PIP5K1α/AKT. We showed that MMP9 physically interacted with PIP5K1α via formation of protein–protein complexes. Furthermore, elevated expression of MMP9 enhanced ability of AR to activate its target gene cyclin A1. The elevated sequential activation of AR/PIP5K1α/AKT/MMP9/VEGF signaling axis contributed to increased invasiveness and growth of metastatic tumors. Conversely, treatment with PIP5K1α inhibitor significantly suppressed invasiveness of PCa cells expressing constitutively activated AR, this was coincident with its inhibitory effect of this inhibitor on AR/MMP9/VEGF pathways. Our results suggest that AR and MMP9‐associated network proteins may be effectively targeted by blocking PIP5K1α/AKT pathways using PIP5K1α inhibitor in metastatic PCa. Abstract : What's new? The androgen receptor (AR) is a key factor in prostate cancer (PCa) progression and metastasis. Given that matrix metalloproteinase 9 (MMP9) and the vascular endothelial growth factor (VEGF) pathway are critical for tumor vascularization and invasion under castration‐resistant condition, it may be of importance to define the functional interplay between AR and MMP9 and their associated key survival and invasion pathways in PCa cells. This study identifies novel cooperative mechanisms involving AR, the MMP9/ VEGF signaling axis and PIP5K1α/AKT pathways driving tumor invasion. The findings provide new information to guide the development of targeted therapy for invasive castration‐resistant prostate cancer.